Analisis Pengaruh Supply Chain Integration, Teknologi Informasi dan Inovasi Terhadap Keunggulan Bersaing pada Perusahaan Freight Forwading - Rahmasari, Lisda (Jurnal Ilmiah Aset, 2019)
This study aimed to find out the influence of supply chain integration, information technology and innovation on competitive advantage. The research population comprised freight forwading company in Semarang City. The sample was selected by means of the purposive sampling technique. The sample was 100 companies. The data were collected by a questionnaire, interviews, and documentation. The data analysis technique in the study was multiple regression analysis using the program of SPSS Version 17 for Windows. The results of the study showed that supply chain integration, information technology and innovation had a significant positive effect on competitive advantage. The coefficient of determination (R2) is 0.71 or 71%, the coefficient shows that 71 % of competitive advantage is affected by supply chain integration, information technology, innovation while the remaining 29% is affected by other independent variables not study.